2000
DOI: 10.3354/meps207079
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of Sargassum muticum in Limfjorden (Denmark) and its possible impact on the indigenous macroalgal community

Abstract: Attached Sargassum muticum (Yendo) Fensholt was first observed in the westernmost part of Limfjorden (Denmark) in 1984, and it has since colonized Limfjorden from west to east at a rate of 15 to 17 km yr -1. By 1997, S. muticum had become the most dominant macroalga, covering more than 6% of the bottom between 0 and 6 m depth, corresponding to ca 35% cover of the hard substrate. In 1990, the cover of S. muticum was strongly correlated with distance from the original source area in the westernmost part of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
137
3
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(150 citation statements)
references
References 34 publications
9
137
3
1
Order By: Relevance
“…Since S. muticum stocks are increasing in European waters (e.g. Critchley et al 1987, Karlsson & Loo 1999, Staehr et al 2000, a subject of further research should be whether these stocks could potentially trigger the high abundances of snake pipefish currently found in the northeast Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since S. muticum stocks are increasing in European waters (e.g. Critchley et al 1987, Karlsson & Loo 1999, Staehr et al 2000, a subject of further research should be whether these stocks could potentially trigger the high abundances of snake pipefish currently found in the northeast Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…After establishment, densities of S. muticum have strongly increased along European coasts (e.g. Critchley et al 1987, Karlsson & Loo 1999, Staehr et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated negative impacts by S. muticum on indigenous algal assemblages (Fletcher and Fletcher 1975;Ambrose and Nelson 1982;Viejo 1997;Cosson 1999;Staehr et al 2000) but only a limited number of studies have addressed the possible consequences for macroalgal epibiota. Those that have, have suggested few adverse effects, apparently due to a low degree of habitat specificity among the epibiota (Withers et al 1975;Jephson and Gray 1977;Viejo 1999).…”
Section: Introductionmentioning
confidence: 99%
“…When non-indigenous species invade new communities, they interact with and have effects on many resident species (Staehr et al 2000;Crooks 2009;Altieri et al 2010). Similar to any other ecological network of interactions, this leads to some residents being adversely affected while others benefit.…”
Section: Introductionmentioning
confidence: 99%